2022
DOI: 10.1149/1945-7111/aca129
|View full text |Cite
|
Sign up to set email alerts
|

Perspective—Trends in the Miniaturization of Photosynthetic Power Cell towards Improved Power Density

Abstract: Microphotosynthetic Power Cells (µPSCs) have emerged as a promising bioelectricity generation technology with the potential to meet the low power application demand in a sustainable, and environmentally friendly manner by leveraging the photosynthetic capabilities of autotrophic microbes, which rely on sunlight and water to produce energy. Over the years, various materials and/or structural designs have been investigated in an effort to enhance performance. These designs have come in a range of inconsistent si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The current miniaturized solutions for sensor networks require ad hoc solutions that are, in most cases, not yet industrialized [ 122 , 123 ]. The harvesting technique employed in geohazard monitoring can surely benefit from miniaturized solar cells [ 124 ] to reduce the nodes’ dimensions. The employment of machine learning and artificial intelligence has various application possibilities in geohazard monitoring and is currently a very studied field [ 125 ].…”
Section: Considerations On the State Of The Art And Future Perspectivesmentioning
confidence: 99%
“…The current miniaturized solutions for sensor networks require ad hoc solutions that are, in most cases, not yet industrialized [ 122 , 123 ]. The harvesting technique employed in geohazard monitoring can surely benefit from miniaturized solar cells [ 124 ] to reduce the nodes’ dimensions. The employment of machine learning and artificial intelligence has various application possibilities in geohazard monitoring and is currently a very studied field [ 125 ].…”
Section: Considerations On the State Of The Art And Future Perspectivesmentioning
confidence: 99%
“…made a three-electrode BPV with Chlorella vulgaris and Rhodopseudomonas palustris as biological materials, and found that the potential required to extract electrons from the latter was lower, and had lower dependence on external electron mediator. Besides biological combination, BPV can also be combined with other electrical devices to improve current output efficiency, such as self-charging supercapacitors ( Das et al., 2018 ; Liu and Choi, 2020a ; Liu and Choi, 2020b ; Powell et al., 2021 ; Alajmi et al., 2022 ; Pankratova et al., 2022 ) or more complex boost converters ( Hill and Bendall, 1960 ; Singh and Pandit, 2013 ; Oseyemi et al., 2022 ).…”
Section: Biological Materials Used In Bpvmentioning
confidence: 99%